2019
DOI: 10.1038/s41598-019-45610-4
|View full text |Cite
|
Sign up to set email alerts
|

The radiation environment of anaesthesiologists in the endoscopic retrograde cholangiopancreatography room

Abstract: Anaesthesiologists are increasingly involved in nonoperating room anaesthesia (NORA) for fluoroscopic procedures. However, the radiation exposure of medical staff differs among NORA settings. Therefore, we aimed to investigate the radiation environment generated by fluoroscopic endoscopic retrograde cholangiopancreatography (ERCP) and the radiation exposure of anaesthesiologists. The dose area product (DAP), radiation entrance dose (RED), and fluoroscopy time (FT) according to the procedures and monthly cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Many reports have shown that occupational dose to the lens of the eye is significant among physicians involved in clinical radiation care over many hours, such as interventional radiology (IR) of the neurovascular system [6,7,8,9], cardiovascular system [8,10] or tumor [8,9,11], and endoscopic retrograde cholangiopancreatography (ERCP) [8,12,13,14]. The risk of radiation-induced cataracts is widely recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have shown that occupational dose to the lens of the eye is significant among physicians involved in clinical radiation care over many hours, such as interventional radiology (IR) of the neurovascular system [6,7,8,9], cardiovascular system [8,10] or tumor [8,9,11], and endoscopic retrograde cholangiopancreatography (ERCP) [8,12,13,14]. The risk of radiation-induced cataracts is widely recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians performing ERCP must be educated to reduce radiation exposure in children. Moreover, medical staff, including endoscopists, assistants, and anesthesiologists, must be protected from radiation exposure during ERCP procedures 43–46 …”
Section: Awareness Of Radiation Exposure In Childrenmentioning
confidence: 99%
“…Moreover, medical staff, including endoscopists, assistants, and anesthesiologists, must be protected from radiation exposure during ERCP procedures. [43][44][45][46]…”
Section: Awareness Of Radiation Exposure In Childrenmentioning
confidence: 99%
“…Fluoroscopic imaging is commonly used either with a `C-arm´or in designated satellite suites or hybrid theatres with embedded fluoroscopy imaging machines [1,2]. Fluoroscopy is a convenient tool for capturing images when other means, such as X-ray radiography and computed tomography are not readily accessible.…”
Section: Introductionmentioning
confidence: 99%